Religions Stand for Protection not for Domestic Violence - Bilal Ahmad Bhat; Nazia Fayaz Azad; Iqra Firdous (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2025)
A woman whether she is married or unmarried seems to be the lesser child of God because the domestic violence (which is attributed usually to the in-laws) starts even before she comes into the world as at times a foetus that carries a female is either aborted or if the girl-child is born, she is killed. It’s a proven fact even in the 21st century that in many families, girls are attended to after the boys have been cared for. Woman is the foundation of a family, gives birth to a new life, nurtures and shapes it, preserves and transmits culture from generation to generation; the irony is that she is subjected to domestic violence irrespective of her age, race, and caste, social, economic and political status. Her vulnerability in various forms is the common phenomenon in the Indian society. Her silent sufferings are making her an easy prey to the male domination which is supported by the patriarchal society that we live in. Almost every home in India must be suffering from some kind of domestic violence where women either as a daughter, daughter in law or as a wife are abused physically, mentally, verbally or even economically. If she speaks up then she is labelled as disobedient and rude. Though theoretically men and women have equal rights but still a woman is discriminated and this at times makes her unable to understand her own right and freedoms. Thus domestic violence not only hampers women but it’s also a hindrance to a country’s growth. This paper deals with the menace of domestic violence and how the different religions deal with this problem as at the end it’s not just about the laws but also about the morals.